Study of recurring typhus in Peru (Concussion) - Del Prado, Eliodoro (1920)
We will just briefly indicate the gross changes, which we have been possible to find in the autopsy of one fatal case count in our statistics Lazaretto La Mar. The microscopic lesions have studied many authors among which we can mention BESANCON, PONFIK, etc.